(untitled) (Journal for Studies in Humanities and Social Sciences, 2017)
This study examined challenges that student teachers placed in rural schools in the two Kavango regions of Namibia encounter during practicum placements. A sample of 15 participants that consisted of five assessors (teacher educators) who had visited more than one of the selected rural schools and ten student teachers (team leaders) from three teaching School Based Studies (SBS) phases were selected using stratified purposive sampling. Semi-structured interviews complemented by data from students’ reflective journals were used during data collection. The data was analysed in conformity with content analysis. The identified challenges were grouped into three categories: student related, institution related and school related challenges. The results of the study revealed that student teachers were inadequately prepared by their training institutions to adapt to different school environments. Furthermore, the findings revealed that student teachers were not fully supported by principals and mentor teachers, and that schools were inadequately resourced. Poor infrastructure and under-qualified temporary teachers were reflected by the outcomes of School-Based Studies (SBS) and the quality of the teacher training programmes. As a result, a partnership model to enhance SBS was developed to provide mitigation strategies on how challenges associated with student practicum placements, could be addressed.